Mechanisms of expansions of a pentanucleotide repeat responsible for spinocerebellar ataxia 10. - Cherng, Nicole Binanne. (Tufts Archival Research Center, 2005)
Spinocerebellar ataxia type 10 (SCA10) is an autosomal dominant disease characterized by ataxia and, in some cases, epilepsy, which is caused by expansions of the (ATTCT)n repeat within an intron of the ATXN10 gene. The repeat can expand from 10-22 copies in normal individuals up to 4,500 repeats in SCA10 patients. To understand the mechanisms responsible for (ATTCT)n repeat instability, we set up a genetically controlled system to analyze its expansions in Saccharomyces cerevisiae. By integrating (ATTCT)n repeats into an intron of the selectable gene reporter, we found that they do expand in yeast resulting in the reporter's inactivation. This inactivation is due to the fact that the levels of both unspliced and spliced RNA of the reporter were strongly decreased upon lengthening of the (ATTCT)n repeat in its intron. The rates of expansions dramatically increased with the repeat lengths, mimicking the situation in human pedigrees. We then performed preliminary genetic analysis, by disrupting several genes involved in DNA metabolism. In the Δtof1 strain, the rate of expansions increased 8-fold suggesting that the Tof1 protein acts to prevent (ATTCT)n repeat expansions. In the Δrad5 strain, no expansions were observed, implicating that the Rad5 protein is a crucial factor for expansions. We speculate that expansions of (ATTCT)n repeats could occur upon template switching during the replication of repetitive DNA.